C1q/TNF‐related peptide 8 (CTRP8) promotes temozolomide resistance in human glioblastoma. Issue 9 (2nd August 2018) - Thanasupawat, Thatchawan; Glogowska, Aleksandra; Burg, Maxwell; Krcek, Jerry; Beiko, Jason; Pitz, Marshall; Zhang, Guo‐Jun; Hombach‐Klonisch, Sabine; Klonisch, Thomas
Abstract : The C1q/TNF‐related peptide 8 (CTRP8) has recently emerged as a novel ligand of the G protein‐coupled receptor RXFP1 in the fatal brain tumor glioblastoma (GBM). We previously demonstrated that the CTRP8‐RXFP1 ligand–receptor system promotes motility and matrix invasion of patient GBM and U87 MG cells by specific phosphorylation of PI3 kinase and protein kinase C. Here, we demonstrate a novel role for CTRP8 in protecting human GBM cells against the DNA alkylating damage of temozolomide (TMZ), the standard chemotherapy drug used to treat GBM. This DNA protective role of CTRP8 required a functional RXFP1‐STAT3 signaling cascade in GBM cells. We identified N‐methylpurine DNA glycosylase (MPG), a monofunctional glycosylase that initiates base excision repair pathway by generating an apurinic/apyrimidinic (AP) site, as a new CTRP8‐RXFP1‐STAT3 target in GBM. Upon TMZ exposure, treatment with CTRP8 reduced the formation of AP sites and double‐strand DNA breaks in GBM cells. This CTRP8 effect was independent of cellular MGMT levels and was associated with decreased caspase 3/7 activity and increased survival of human GBM. CTRP8‐induced RXFP1 activation caused an increase in cellular protein levels of the anti‐apoptotic Bcl members and STAT3 targets Bcl‐2 and Bcl‐XL in human GBM. Collectively, our results demonstrate a novel multipronged and clinically relevant mechanism by which the CTRP8‐RXFP1 ligand–receptor system exerts a DNA protective function against TMZ chemotherapeutic stress in GBM. This CTRP8‐RXFP1‐STAT3 axis is a novel determinant of TMZ responsiveness/chemoresistance and an emerging new drug target for improved treatment of human GBM. Abstract : Activation of RXFP1 by CTRP8 induces phosphorylation of the oncogenic STAT3 signaling pathway in human glioblastoma cells. STAT3 phosphorylation mediates the transcriptional upregulation of MPG, resulting in increased MPG activity and enhanced base‐excision repair capability following TMZ treatment. This improved DNA repair capability, together with a STAT3‐induced upregulation of anti‐apoptotic BCL‐2 and BCL‐XL, promotes TMZ chemoresistanceand cell survival upon RXFP1 activation in glioblastoma cells.